Design of a franchise model in the rice bread grocery industry. (Revista Sistemas de Producción Agroecológicos, 2020)
The rice bread industry has consolidated significant growth in recent years, being a typical product of the Meta department and in the search for its expansion into national markets, growth strategies are proposed in the small and medium-sized companies that produce these products; For this purpose, the present project seeks to design a franchise model for the Rice Bread Food Industry, specialized in this production, located in the municipality of Restrepo, Meta, Colombia that allows it to expand its business units and achieve the Strengthening your brand by creating operating manuals that standardize all your processes. It was determined that the structure of the franchise system most suitable for this company is that of production, being the franchisor that provides all the products to the franchisee, which can be distributed ultra frozen and vacuum packed, ready to bake and consume; in this way, the quality of the manufacturing processes is controlled, the brand image is not affected by the loss of the characteristics of the products.
Keywords: rice bread; franchise; operating manuals